Environmental pollution monitoring system based on gas water quality sensors and visual recognition - Guolei Wang (Results in Engineering)
With the development of industrialization and urbanization, environmental pollution is becoming more and more serious, which poses a serious threat to human health and ecosystem. Therefore, this study aims to design and implement an environmental pollution monitoring system combining gas and water quality sensors in order to monitor and identify pollutants in the environment in real time, and use visualization technology to effectively present monitoring results. The study selected high-precision gas and water quality sensors to accurately detect various pollutants in the environment. Integrating these sensors organically into one system ensures that they can work together and achieve seamless transmission and integration of data. Next, data processing algorithm is applied to analyze and process these data, and visualization technology is used to show the monitoring results. An intuitive and friendly graphical interface is designed to show the concentration of pollutants, helping users to understand the environmental pollution more intuitively. The experimental results show that the system can accurately and real-time monitor various pollutants in the environment, and can clearly display the monitoring data. Through the application of the system, users can understand the situation of environmental pollution in time, and provide reliable data support for environmental protection and pollution control.